Competition effect exerted by two nonnative invasive plant species on a native under contrasting conditions of resource availability - Arias, Gonzalo (2023)
Competition between native and nonnative invasive species is a key interaction determining community composition. The identity and number of interacting species plus the level of resource availability can affect the competition outcome. In this study, we performed a greenhouse experiment with seedlings to analyze the intraspecific competition experienced by the native species Lithraea molleoides and the interspecific competition exerted by two nonnative invasive species (Ligustrum lucidum and Pyracantha angustifolia) separately and together, under two contrasting water and light availability conditions. The selected species coexist in the Chaco Serrano mountains in central Argentina. In particular, we found that interspecific competition by the nonnative invasive L. lucidum had a higher negative effect on the performance of the native species than intraspecific competition as well as than interspecific competition by both nonnatives. The negative effect of L. lucidum on the native species showed a tendency to be stronger under higher resource availability. Additionally, a joint effect of both nonnatives on the native species was observed, consisting of a lower root biomass under low water availability. Our results highlight the importance of controlling one of the most important woody invaders in Argentina, but also draw attention on the relevance of measuring numerous traits and different resource conditions to fully evaluate the possible joint effects of nonnatives on native species.